Nelson Mandela’s ‘Ordinary Love’ Addressed in Pop-rock Music: a Long Song of Freedom (Altre Modernità, 2014)
This paper aims to highlight how inspirational the figure of Nelson Mandela has been for several musicians and songwriters. In particular, it focuses on songs written by Western musicians from the early Eighties until 2013 – all showing the extent to which the South African leader has epitomized the struggle for equality and freedom. This study points out how the success of a hit single in 1984 – British ska group The Special AKA’s “Free Nelson Mandela” – paved the way for a quick increase in the number of musicians who got involved in the anti-apartheid movement and contributed to make Western audiences know about Mandela and increasingly demand that apartheid be put to an end. This survey seeks to examine the main achievements in pop-rock songs that generated both from the growing awareness about the South African leader’s experience when he was imprisoned, and the legacy of his exemplum after he was set free. Among the songs cited: Simple Minds’ “Mandela Day”, the various artists’ tribute “46664” and the most recent Golden Globe-awarded “Ordinary Love” by U2, written for the soundtrack of the biopic The Long Walk to Freedom. To better understand how the figure of Mandela has been addressed in these works, the paper includes analyses of the most complex and significant lyrics among the songs discussed, thus also showing how the South African cultural background as it was received by the West could have informed the songwriting, and how the Western reception of such songs determined an increasing awareness about Mandela’s plight and the whole phenomenon of apartheid.